Cytoprotective Effect of Lacritin on Human Corneal Epithelial Cells Exposed to Benzalkonium Chloride In Vitro. (8th January 2014) - Feng, Mary M.; Baryla, Julia; Liu, Hong; Laurie, Gordon W.; McKown, Robert L.; Ashki, Negin; Bhayana, Dinesh; Hutnik, Cindy M. L.
Abstract: Purpose : Benzalkonium chloride (BAK) is the most commonly found preservative in eye drops, and has been shown to cause ocular surface inflammation and toxicity. Lacritin is a human tear glycoprotein secreted from the lacrimal glands that has been found to be cytoprotective. This study was designed to determine if the presence of lacritin confers protection to a cultured human corneal epithelial (HCE) cell line, CRL-11515, and primary HCE cells after exposure to the ocular preservative agent BAK. Materials and methods : Recombinant human lacritin was cloned into intein fusion vectors, expressed in E. coli, and purified on chitin beads and DEAE Sepharose. Metabolic curves were established using the MTT assay after exposure of sub-confluent CRL-11515 cells to BAK or lacritin. Western blot analysis of lipidated LC3 (LC3-II) provided a measure of autophagy in CRL-11515 cells exposed to lacritin and/or BAK. Results : BAK reduced CRL-11515 cellular metabolic activity in a time- and dose-dependent manner. BAK-induced cellular stress was evident by elevated autophagy that increased with rising concentrations of BAK compared to control ( p  < 0.05). Lacritin increased HCE cell proliferation at an optimal dose of 1 nM. Preconditioning HCE cells with 1 nM lacritin for 24 h prior to BAK exposure significantly dampened levels of LC3-II ( p  < 0.05) and promoted a significant increase in cellular metabolic activity ( p  < 0.01) compared to BAK alone. Conclusions : These results suggest lacritin protects cultured HCE cells stressed with BAK. Lacritin may have the potential to be used as a topical adjunctive therapy in eyes chronically exposed to BAK.